(3GdCZGfjs - (3Ydj Hf GdMSjf Hf eMeO Hf CMeO Hf GdgjKe GdeQhGfj GdCehj GdbQTj, CHh GdaQL GdCUHgGfj, J (B356 (3g` s ((3YHOGdQShd Hf YHOGdbGOQ GddGghQj s)
(3ChdgG (B:s
(3GdMeO ddg hMOg, hUdGJg Ydi fHjfG NGUI gPG cJGH Cdag Ydj Hf GdMSjf GdCUagGfj hLeY ajg eG MVQg hCecfg LeYg ef GdCZGfj GdYQHjI bOjegG hMOjKgG, hfSH cd eG PcQ efgG Edi bGFd TYQg s
(3BNQgG (B:s
(3dh SeYJ GdZfGA, dh SFdJ dCYWjJ, hdh dbjJ YfOgG dHcjJ, abGd eYGhjI(B: (3bHM Gddg bheG YQVhfj dc Ke NQL hHYK Edjg HUdI, hjJdhg UhJ CjgG GdbdH dG CQGc Jajb Edi BNQ GdCHjGJ s
(3GfXQ GdLRA GdChd HQbe (B41-52 (3COHs
(3heNJGQ GdCZGfj HGdCQbGe (B732-737 (3COHs
(3LGA Ydi GdHWGbI GdeUhQI eY GdcJGH eNJGQ GdCZGfj hgh NWCs
(3hQO CjVkG JMJ Qbe (B2176 s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B278 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B78s
Keywords: (3GdCOHs